1996
DOI: 10.1542/peds.97.5.688
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physical Outcome of Children Conceived by In Vitro Fertilization

Abstract: Objective. To determine the growth and physical outcome at 2 years of age for children born after assisted reproductive techniques in the state of Victoria. Design. Using a case-matched control study between January 1991 and July 1993, 314 children (196 singletons, 47 sets of twins, 8 sets of triplets) conceived after in vitro fertilization (IVF) and related techniques at the Monash IVF and Royal Women's Hospital Reproductive Biology Unit and 150 control children (113 singletons, 17 sets of twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Assisted reproduction information is not always available to follow-up personnel; however, when these cohorts were followed, an independent effect of in vitro fertilization on growth and neurological outcomes was not seen (12). It is estimated that because of the increased numbers of multiples associated with ARTs, they now contribute 8% to the annual number of CP cases.…”
Section: Assisted Reproductionmentioning
confidence: 99%
“…Assisted reproduction information is not always available to follow-up personnel; however, when these cohorts were followed, an independent effect of in vitro fertilization on growth and neurological outcomes was not seen (12). It is estimated that because of the increased numbers of multiples associated with ARTs, they now contribute 8% to the annual number of CP cases.…”
Section: Assisted Reproductionmentioning
confidence: 99%
“…Recently, some studies showed that the outcomes of ART infants were similar to those of spontaneously conceived infants 12 . Differences in the outcomes of ART and spontaneous pregnancies (SPs) were due to confounders, such as male or female infertility 13,14 and multiple pregnancy, 15 with IFTs themselves having a negligible impact on infant outcomes 16–19 . A consensus has not yet been reached on whether IFTs themselves affect infant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…12 Differences in the outcomes of ART and spontaneous pregnancies (SPs) were due to confounders, such as male or female infertility 13,14 and multiple pregnancy, 15 with IFTs themselves having a negligible impact on infant outcomes. [16][17][18][19] A consensus has not yet been reached on whether IFTs themselves affect infant outcomes. If such an influence exists, IFTs increase infant morbidity and mortality, thereby overtaxing the limited number of beds available in neonatal intensive care units (NICU).…”
Section: Introductionmentioning
confidence: 99%